Mechanisms of Csp3‐H or Nsp2‐H functionalization of 2, 3‐diaminoindoles with triplet O2: A density functional theory investigation. (9th September 2020) - Deng, Zhe‐Peng; Zhou, Da‐Gang
Abstract: The mechanisms of Csp 3 ‐H or Nsp 2 ‐H activations of 2, 3‐diaminoindoles oxidized by triplet O2 have been investigated with the method of M06‐2X‐D3/6‐31 + G(d, p) in the Universal Solvation Model Based on Solute Electron Density (SMD) model. The calculations indicate that the activation of 2, 3‐diaminoindoles has three possible paths. First, the Csp 3 ‐H functionalization has a higher energy barrier than that of Nsp 2 ‐H activation; then an intramolecular H‐shift reaction happened to lose a H2 O2 molecule; the third step is a ring‐closure reaction and imidazolo‐indole skeleton would be constructed; finally, the elimination reaction occurred, and the final product would be yielded. Fukui function and dual descriptor could be used to predict the active sites of the reactants and intermediates. Results would provide valuable insights into these types of interactions and related ones. Abstract : The mechanisms from 2, 3‐diaminoindoles to imidazo[4, 5‐b]indoles oxidized by triplet O2 were elaborated based on DFT calculations.